Empirical Research of the Knowledge Degree of Social Economy Enterprises in Stable Micro-communities - Popescu, Dan; State, Cristina; Nicolae, Valentina; Pavel, Ioana (European Journal of Sustainable Development, 2016)
The social economy, as the correct solution to solving the problems of a community, tends to take shape in Romania too: an evidence of this, is the recently promulgation of the law regulating the activity of these economic entities, generically named social economy enterprises, or social enterprises, that work in this sector. The first research question that we intend to answer in the paper regarding on "Improving the management of social economy enterprises, an essential factor in sustainable and responsible development of local communities", relates to the definition of social economy concept, followed naturally by another one, in connection with the knowledge degree of the social economy sector. Work methodology that we use consists in an exploratory research, based on a semi-structured questionnaire, directly administered, in a micro-stable community that we observe since 2002. Interpretation of responses received from participants in the study was performed using the IBM SPSS 20 application. The variables obtained were analysed both from the point of view of descriptive statistics and also, by the correlations that have been established between them. The results from testing hypotheses, confirms our assumptions, according to that, the subjects participating in the study had, at the time of performing the survey, very little information regarding to the social economy. Extensive research is ongoing, following that in the next period we will be able to present, new, additional information able to complete the overview on the field of study. Keywords: empirical research, improving management, communities, social enterprise, sustainable development JEL Classification: C120, D630, M200, M210, O350